Is It True That Digital Time Management Applications Can Increase Students' Learning Motivation? - Putri Ramadhani Lubis; Silvia Mariah Handayani (PT. Global Research Collaboration, 2025)
The rapid development of digital technology has encouraged students to utilize time management applications as a strategy to organize their learning activities more effectively. This study aims to examine the influence of digital time management application usage on students’ learning motivation. A quantitative approach with a cross-sectional survey design was employed, involving 65 students selected through a non-probability sampling technique. The research instrument consisted of a Likert-scale questionnaire that had passed validity and reliability testing. Data were analyzed using descriptive statistics and linear regression. The results reveal that the use of digital time management applications has a significant and strong effect on students’ learning motivation. These findings demonstrate that digital applications assist students in establishing structured learning routines, enhancing focus, and strengthening self-regulation toward their academic goals. In conclusion, digital time management applications can serve as an effective strategy to improve students’ learning motivation in the digital era.